Inflation Versus Prime Lending Rates: An Empirical Analysis - Chandran, Deepa; Francis, Philo (Indian Journal of Finance, 2014)
The inflation rate in our country increased significantly during the last six years. The Reserve Bank of India has been using high interest rate policies to contain the excessive instability and the excessive money supply in the economy. In this context, the present study has attempted to analyze the relationship between inflation rate and prime lending rate in India. The study was mainly limited to the prime lending rates of SBI and ICICI Bank. The time period of the study is from 2004 to 2011. For the purpose of analysis, the inflation rate was compared with the prime lending rates of SBI and ICICI Bank with the help of correlation, regression, and ANOVA tools. The analysis lead to the finding that for most of the years, inflation and prime lending rates of the 2 banks were negatively correlated. However, after testing the fit of the regression line, a conclusion was at arrived that there was no significant relationship between inflation rates and SBAR; whereas, there was a significant relationship between inflation rates and IBAR. Thus, the study tries to provide necessary guidance regarding the relationship between the inflation rates and the prime lending rates.